2019
DOI: 10.1002/smll.201903016
|View full text |Cite
|
Sign up to set email alerts
|

A GSH‐Gated DNA Nanodevice for Tumor‐Specific Signal Amplification of microRNA and MR Imaging–Guided Theranostics

Abstract: Developing tumor‐responsive diagnosis and therapy strategies for tumor theranostics is still a challenge owing to their high accuracy and specificity. Herein, an AND logic gated–DNA nanodevice, based on the fluorescence nucleic acid probe and polymer‐modified MnO2 nanosheets, for glutathione (GSH)‐gated miRNA‐21 signal amplification and GSH‐activated magnetic resonance (MR) imaging–guided chemodynamic therapy (CDT) is reported. In the presence of overexpressed miRNA and GSH (tumor cells), the nanodevice can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 59 publications
(33 reference statements)
1
42
0
Order By: Relevance
“…Furthermore, they have been reported to be closely associated with many kinds of tumors including glioma [9]. Strong evidence has shown that many miRNAs have positive or negative effects on glioma [10]. By comparing miRNA expression in different grades of glioma, studies have revealed potential miRNA functions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they have been reported to be closely associated with many kinds of tumors including glioma [9]. Strong evidence has shown that many miRNAs have positive or negative effects on glioma [10]. By comparing miRNA expression in different grades of glioma, studies have revealed potential miRNA functions.…”
Section: Introductionmentioning
confidence: 99%
“…At 24 h following incubation, only ≈20% of the TMZ was detected in the medium in the former case (M 0 Mφ), whereas about 85% of the TMZ was detected in the latter case (M 1 Mφ). Relative to normal tissue environments, tumor tissue environments are highly reductive with at least fourfold higher concentrations of GSH, [30] which can effectively cleave the disulfide bonds within the prodrug NPs, releasing TMZ. These experimental data suggest that the prodrug/drug release from the Mφ-hitchhiked NPs is limited before they arrive at the tumor site, avoiding systemic cytotoxicity, while efficient prodrug/drug release occurs upon their arrival.…”
Section: Resultsmentioning
confidence: 99%
“…Through the progress in DNA nanotechnology, nano‐level machines/devices have been designed with excellent performance combined with the biological compatibility of DNA, suitable for biomedical applications 82–85 . DNA nanotechnology has become an evolutionary approach for targeting biomolecules in vitro as well as systemically 86–88 . These materials have been investigated for exhibiting improved treatment efficacy and safety profile compared to the prospects of current diagnostic/treatment options 89–91 .…”
Section: Summary and Outlooksmentioning
confidence: 99%